مقارنة فعالية إزالة الكروم من مياه الصرف التركيبية باستخدام الوصل الفردي والوصل المزدوج لأقطاب المخثر الكهربائي - العجي بسام (Latakia University Journal -Engineering Sciences Series, 2017)
In this work, the performance of batch electrocoagulation (EC) treatment using iron electrodes with monopolar and bipolar electrode configurations for trivalent chromium (Cr (III)) removal from a synthetic wastewater was investigated. The influences of current density (from 2 to 25 mA/cm2) and initial metal concentration (from 100 to 250 mg/L) on the removal efficiency were explored in a batch stirred cell for monopolar and bipolar configurations. Removal of Cr (III) by EC process from aqueous solution with both monopolar and bipolar electrode configurations was a feasible process. For the initial Cr (III) concentration of 250 mg/L, almost complete removal (99.88%) of Cr (III) was noted after 20 min of EC in case of bipolar electrode arrangement at 25 mA/cm2 with 4.5 mmol/L of supporting electrolyte (Na2SO4) against 89.58% of Cr (III) removal for monopole electrode configuration. At the same electrolysis time, the power consumption was 47 and 15.3 kWh/m3 in case of monopolar and bipolar configuration respectively for the previous removal conditions. تم في هذا البحث اختبار أداء عملية التخثير الكهربائي الدفقي باستخدام أقطاب الحديد الكهربائية ذات الوصل الفردي والمزدوج، بهدف إزالة الكروم ثلاثي التكافؤ Cr (III) من مياه الصرف التركيبية. كان استخدام كل من الوصل الفردي والمزدوج لعملية التخثير الكهربائي من أجل إزالة الكروم الثلاثي عمليةً ملائمةً. جرت دراسة تأثير كل من كثافة التيار الكهربائي (ضمن المجال من 2 وحتى 25 ميلي أمبير/سم2) وتركيز الكروم الابتدائي (ضمن المجال من 100 وحتى 250 مغ/ل) على كفاءة إزالة الكروم في خلية دفقية مضطربة من أجل كل من الوصلين الفردي والمزدوج. لوحظت إزالة شبه كاملة للكروم الثلاثي % 99.88 من مياه الصرف الحاوية على تركيز أولي للمعدن قدره 250 مغ/ل بعد 20 دقيقة من عمل المخثر الكهربائي في حالة الوصل المزدوج لدى استخدام كثافة تيار كهربائي قدرها 25 ميلي أمبير/ سم2 عند إضافة 4.5 ميلي مول /ل من داعم الالكتروليت مقابل إزالة قدرها % 89.58 لدى استخدام الوصل المفرد. وكان مصروف الطاقة خلال هذه العملية لنفس الشروط السابقة حوالي 47 كيلو واط ساعي/م3 للوصل المزدوج وحوالي 15.3 كيلو واط ساعي/م3 للوصل المفرد من أجل الحصول على نفس الفعالية السابقة.